Il linguaggio dell'odio Fra memoria e attualità - D'Amico, Marilisa; Brambilla, Marina; Crestani, Valentina; Fiano, Nannerel (I diritti negati, 2021)
The book illustrates, between past and present, the impact of hate speech on actions, investigating, more precisely, the different languages that have conveyed, witnessed or sanctioned forms of hate. The book offers a multi-disciplinary perspective, including essays of historical, social, linguistic, literary and juridical-social nature in order to identify the forms of hate speech.